Direct gene delivery of human tissue kallikrein reduces blood pressure in spontaneously hypertensive rats. - Wang, C (1995)
Hypertension is a multigene and multifactorial disorder affecting approximately 25% of the population. To demonstrate potential therapeutic effects of human tissue kallikrein in hypertension, spontaneously hypertensive rats were subjected to somatic gene therapy. Two human tissue kallikrein DNA constructs, one under the promoter control of the metallothionein metal response element and the other under the control of the Rous sarcoma virus 3'-LTR, were generated. We delivered naked DNA constructs into spontaneously hypertensive rats via intravenous injection. The expression of human tissue kallikrein in rats was identified in the heart, lung, and kidney by reverse transcription polymerase chain reaction followed by Southern blot analysis and an ELISA specific for human tissue kallikrein. A single injection of both human kallikrein plasmid DNA constructs caused a sustained reduction of blood pressure which began 1 wk after injection and continued for 6 wk. A maximal effect of blood pressure reduction of 46 mmHg in rats was observed 2-3 wk after injection with kallikrein DNA as compared to rats with vector DNA (n = 6, P < 0.05). The hypotensive effect caused by somatic gene delivery of human tissue kallikrein in hypertensive rats is reversed by subcutaneous injection of aprotinin, a potent tissue kallikrein inhibitor. No antibodies to either human tissue kallikrein or kallikrein DNA were detected in rat sera after injection of the human kallikrein gene. These results show that direct gene delivery of human tissue kallikrein causes a sustained reduction in systolic blood pressure in genetically hypertensive rats and indicate that the feasibility of kallikrein gene therapy for treating human hypertension should be studied.